Ambiguitas Nomenklatur Kementerian, Lembaga Pemerintah, dan Lembaga Pemerintah Non Kementerian (LPNK) pada Kabinet Merah Putih - Dian Agung Wicaksono; Garuda Era Ruhpinesthi (Fakultas Hukum Universitas Islam Indonesia, 2025)
During Prabowo Subianto's leadership, various presidential institutions were established, including ministries, non-ministerial government institutions (LPNK), and other government agencies, each with different names. The formation of these institutions raises important questions regarding their characteristics, particularly concerning their scope of authority, organizational position, and the appointment of their leaders. Additionally, this highlights potential ambiguities in their regulations. This study addresses two key questions: (a) How are the ministries, government institutions, and non-ministerial government institutions organized within the Cabinet? (b) What ambiguities exist in the nomenclature of ministries, government institutions, and non-ministerial government institutions in the Cabinets? This research employs a normative legal approach, utilizing both statutory and conceptual analyses. The findings indicate that the institutional mapping within the Cabinets includes 7 coordinating ministries, 41 ministries, 8 LPNK, and one government institution. Furthermore, ambiguities exist in the regulations concerning these three types of presidential institutions, specifically regarding their scope of authority, organizational positions, and leadership structures.